PENGARUH PEMBERIAN INTERVENSI BIRTHBALL TERHADAP KEMAJUAN PERSALINAN KALA 1 FASE AKTIF - Annisa Ramadhani; Fania Nurul Khoirunnisa; Nor Asiyah (Nusantara Hasana Journal, 2026)
Prolonged labor in the first stage is defined as an extended latent phase and an extended active phase. The latent phase is considered prolonged when cervical dilation remains less than 4 cm after 8 hours of regular uterine contractions (more than two contractions within 10 minutes). Meanwhile, a prolonged active phase refers to inadequate cervical dilation progress after the diagnosis of the active phase of the first stage has been established, characterized by cervical dilation of less than 1 cm per hour for at least 2 hours despite ongoing labor progress, and a total duration exceeding 12 hours from 4 cm dilation to complete cervical dilation. Women experiencing prolonged labor are at increased risk of postpartum hemorrhage due to uterine atony, birth canal lacerations, infection, maternal exhaustion, and shock. For the fetus, prolonged labor elevates the risk of severe asphyxia, cerebral trauma, infection, and injury resulting from obstetric interventions. This study aimed to determine the effect of the birth ball intervention on the progress of labor during the active phase of the first stage. A quasi-experimental research design was employed, assessing the duration of the active phase of the first stage of labor using an observation sheet. The study utilized a two-group posttest-only design. The intervention group received the birth ball method, while the control group engaged in light ambulation within the room. Data analysis was conducted using univariate and bivariate approaches. Normality was assessed using the Shapiro–Wilk test, and hypothesis testing was performed using the independent samples t-test. The results of the bivariate analysis using the t-test revealed a p-value of 0.005 (< 0.05), indicating a statistically significant difference between the intervention and control groups in terms of progress during the active phase of the first stage of labor. The mean duration of the active phase in the control group tended to be longer than that in the intervention group. This study demonstrates that the birth ball intervention has a significant effect on the progress of labor during the active phase of the first stage.